TRANSPARENCY PORTAL: A COMPARATIVE STUDY BETWEEN PORTO ALEGRE AND PELOTAS CITIES - Hosser, Carla (2015)
The approval of Complementary Law No. 131/2009 of the Presidency of Republic, assured the citizen monitoring and knowledge of the actions of public bodies in relation to budget execution. In this context, this research was developed in order to analyze the Portals of Transparency of Gaúchos Municipalities of Pelotas and Porto Alegre, in order to in order to analyze the content available on the portals of transparency of such municipalities. Methodologically, it is a documentary study, with descriptive and qualitative approach, developed with use of the content analysis technique to analyze the information published by the municipalities studied. Data collection was guided by the instrument provided by the Associação Contas Abertas, which uses a data rate to be analyzed so that a portal can be considered transparent. These research results demonstrate that, in some cases, the transparency portals studied gather additional information to those required by the Associação Contas Abertas, however, despite providing a significant contingent of information several items proposed in the methodology that association are not being contemplated. In summary, the findings indicate that both cities have the opportunity to improvements to be made in their portals for a more efficient disclosure, which could be materialized through the creation of tools to improve the search of data and strategies that seek to profile the user information for it to be produced in a targeted manner, in other words, with appropriate language.